Le Poulet Co / Mohamad Azam Abd. Aziz ...[et al.] - Abd. Azizi, Mohamad Azam; Mahadi, Mohd Nabil Fikri; Musa, Nur Syafiqah; Hakim, Nuralliah; Syed Hud, Sharifah Amalina (2013)
LE POULET CO not only produces chicken but also produces organic fertilizer. Our company is build with the main objective which is supplying Halal product and make the consumer especially Muslim confident to buy our chicken. Other than that, we want to be the most successful chicken poultry company.